Air pollution and child obesity: Assessing the feasibility of measuring personal PM2.5 exposures and behaviours related to BMI in preschool-aged children in China. (December 2019) - Ong, Hilary; Holstius, David; Li, Yan; Seto, Edmund; Wang, May
Abstract: Background: Accumulating evidence suggests that air pollutant exposures affect multiple metabolic functions which may place populations at a higher risk for obesity. A pilot study was conducted to assess the feasibility of measuring personal exposures to fine particulate matter (PM2.5) and tobacco smoke, to assess the influence of these exposures on the risk of obesity in children in Kunming, a rapidly developing city in China. Methods: We recruited 52 children ages 4–5 years from three preschools in Kunming. Individual-level PM2.5 exposures were assessed using real-time personal monitors. Tobacco smoke exposures were assessed by a parent-reported questionnaire. Results: Subjects' daily mean PM2.5 exposure (n = 52) was 32.8 (SD = 13.4) μg m −3 and daily tobacco exposure was 14.4 (SD = 21.1) cigarettes day −1 . Our subjects' daily mean exposure to PM2.5 was 31% higher than the level set by the WHO daily ambient concentration guidelines. Conclusion: We found personal PM2.5 monitoring to be a feasible method for measuring exposure to PM2.5 in young children. Future studies with larger sample sizes are warranted to explore the relationship between air pollution exposure and risk of obesity in China. Highlights: China has one of the worst air pollution levels in the world. Air pollutants are endocrine disrupting chemicals that can increase obesity risk. We presented novel and feasible methods to measure air pollutant exposure and obesity risk in young Chinese children. We provide evidence to justify conducting epidemiologic studies of environmental risk factors for child obesity in China. This study informs future research studies on environmental pollution and chronic metabolic diseases.